Eveningness is Associated with Higher Risk-Taking, Independent of Sex and Personality. Issue 3 (December 2014) - Ponzi, Davide; Wilson, M. Claire; Maestripieri, Dario
This study tested the hypotheses that eveningness is associated with higher risk-taking propensities across different domains of risk and that this association is not the result of sex differences or confounding covariation with particular personality traits. Study participants were 172 men and women between 20 and 40 years of age. Surveys assessed chronotype, domain-specific risk-taking and risk-perception, and Big Five personality dimensions. Eveningness was associated with greater general risk-taking in the specific domains of financial, ethical, and recreational decision making. Although risk-taking was associated with both risk perception and some personality dimensions, eveningness predicted risk-taking independent of these factors. Higher risk-taking propensities among evening types may be causally or functionally linked to their propensities for sensation- and novelty-seeking, impulsivity, and sexual promiscuity.